Kolaborasi Komik Strip Digital sebagai Media Literasi Covid-19 di Masa Pandemi Covid-19 - Hilman Ahdi Bhaskara (Universitas 17 Agustus 1945 Surabaya, 2024)
Covid-19, which is spreading throughout the world, has made major changes to human life. On the other hand, irresponsible information in the form of hoaxes is spread on various social media and adds to public panic. In response to the confusing information regarding Covid-19 and the widespread problems in society, many social communities have emerged that are moving and consistently trying to provide insight regarding Covid-19. So many social campaigns emerged in the form of visual literacy related to Covid-19 which were adopted by several social media activists, one of which was Koomik.id as a community that collaborated with many local Indonesian comic artists. Koomik.id, invites several local comic artists to collaborate using online methods as a new method due to limited access and space. This research uses semiotics and visual rhetoric studies as according to Tracy Owens Patton in developing Sonja K. Foss' theory of visual rhetoric (Josephson, 2020). The results of the study carried out show that the Covid-19 phenomenon, which has limited the space for comic artists to work creatively, has actually created a breakthrough for the Koomik community in carrying out promotions. The meaning and message to be conveyed from the comic strip collaboration focuses on social problems that exist in society. Covid-19 is not only a problem in the health sector, but also a social problem for confused people.